The Distinctive Nature of Thyroid MALT Lymphomas Including IRTA1 Expression. (12th March 2023) - Carlsen, Eric D.; Davis, Adam R.; Cook, James R.; Swerdlow, Steven H.
Abstract : Mucosa-associated lymphoid tissue (MALT) lymphomas often express IgM and IRTA1 with only a minority demonstrating plasmacytic differentiation. However, like primary cutaneous marginal zone lymphoproliferative disorders (PCMZLPD), thyroid MALT lymphomas (T-MALT-L) frequently show plasmacytic differentiation and IgG positivity. Whether T-MALT-L share other features with PCMZLPD, including frequent IgG4 positivity and infrequent IRTA1 expression, and how IRTA1 staining compares to that in Hashimoto thyroiditis (HT) are unknown. Therefore, the clinicopathologic features of 18 T-MALT-L were assessed, and their IRTA1 expression compared with that in 5 HT cases. All T-MALT-L cases included a B-lymphoid component. Plasmacytic differentiation was present in 15 cases and was extensive in 12. Fourteen cases were IgG+ including 2 IgG4+ (12 κ+, 2 κ−/λ−). One case was IgAλ+. Plasmacytic cells were uniformly CD19+/CD56− but CD138− in 7/15 cases. IRTA1+ cells were present in 16/16 cases, ranging from scattered cells to >50%. They were often concentrated in "MALT ball"-type lymphoepithelial lesions, perifollicular regions, and sometimes in germinal centers. IRTA1 positivity was also present in all HT cases, although it was never very extensive and often had a perifollicular distribution, occasionally with sparse aggregates and positive cells within rare thyroid follicles. Thus, T-MALT-L share some features with PCMZLPD but are more similar to noncutaneous MALT lymphomas, with prominent lymphoepithelial lesions, ubiquitous although variable IRTA1 positivity, and infrequent IgG4 positivity. Plasmacytic differentiation is also common although CD138 loss is frequent and light chain staining may be absent. IRTA1 staining may help in the differential diagnosis with HT, although there is some overlap in staining patterns.